Encapsulation of fish oil, a triglyceride rich in polyunsaturated fatty acids, within a maillard reacted lecithin-dextrose matrix - Dila Donmez; Jasper Limon; Juan Pablo Russi; Alejandro E. Relling; Ken Riedl; Manjunath Manubolu; Osvaldo H. Campanella (Journal of Agriculture and Food Research)
The physicochemical properties and oxidative stability of encapsulated fish oil in a matrix formed by the reaction of crude de-oiled soy lecithin and dextrose following a Maillard reaction path were investigated. The effects of sugar content in formula (4, 8 %) and temperature (25 °C, 80 °C, and 100 °C) on the moisture content, water activity, encapsulation efficiency (EE), and oxidative stability were studied. Oxidative stability was measured over a 90-day testing period at 25 °C. Samples achieved an encapsulation efficiency in the range 50–70 %, low moisture content (<1 %), and low water activity (<0.7). After 90 days of storage, the encapsulated fish oil samples remained within the rancidity limits defined by the peroxide and p-anisidine values, whereas unprotected/free fish oil (control) significantly exceeded those limits. Samples prepared at 100 °C showed the greatest encapsulation efficiency and oxidative stability among the treatments (p < 0.05). The presence of Maillard Reaction Products (MRP) in the encapsulating material was also assessed.